CALCULATION OF UNSTEADY FILTRATION IN GROUND DAMS WITH FORMATE DRAINAGE TAKING INTO ACCOUNT THE FILTRATION ANISOTROPY OF SOILS - Fayziev Homithon; Khozhiev Tozhi Koirovich; Khazhiev Ikrombek Ozodovich; Baymatov Shakhriddin Khushvaktovich; Kholikov Mirkamol Bozor ugli (Zeta Repository, 2023)
The article presents a numerical method for calculating non-stationary filtration in soil dams with reservoir drainage, taking into account the filtration anisotropy of soils.